INFLUENCE OF BRONCHOLYTIC THERAPY ON VENTRICULAR RHYTHM DISORDERS IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Kh. Kh. Shugushev; M. V. Gurizheva; V. M. Vasilenko (Столичная издательская компания, 2016)
Aim. To evaluate effects of broncholytic therapy on ventricular rhythm disorders and high resolution electrocardiogram indices in patients with chronic obstructive pulmonary disease (COPD).Material and methods. 144 patients (54 women and 90 men; aged 47,1±1,5 y.o.) with COPD and 35 patients of control group without respiratory and cardiovascular diseases (23 men and 12 women; aged 42,4±2,8 y.o.) were examined. 24-hour ECG monitoring and high resolution ECG with time and spectral-time mapping of ventricular ECG complex were performed in patients additionally to routine examination.Results. Reduction of ventricular rhythm disorders rate was detected during therapy with extended-release theophylline or salmeterol/fluticasone in patients with moderate and severe COPD. This effect was more significant for salmeterol/fluticasone treatment. Treatment with extended-release theophylline led to increase of a number of ventricular extra systoles in patients with severe COPD. Salmeterol/fluticasone treatment did not influence number of ventricular extrasystoles. Broncholytic therapy had positive influence on processes of ventricular depolarization. It was shown by high resolution ECG indicators improvement and by late ventricular potential rate reduction.Conclusion. Salmeterol/fluticasone combination is more reasonable than extended-release theophylline for broncholytic therapy in patients with severe COPD and ventricular rhythm disorders.